Hypertrichosis cubiti, a case report and literature review. Issue 2 (9th December 2015) - Tng, Vivian E.T.; de Zwaan, Sally
Key Clinical Message: Hypertrichosis cubiti is an uncommon congenital hypertrichosis with links to genetic syndromes, both autosomal dominant and recessive, with variable penetrance and expressivity. It may also present in sporadic cases with no phenotypic abnormalities or family history. Abstract : Hypertrichosis cubiti is an uncommon congenital hypertrichosis with links to genetic syndromes, both autosomal dominant and recessive, with variable penetrance and expressivity. It may also present in sporadic cases with no phenotypic abnormalities or family history.